The Role of Graphene in Enhancing the Material Properties of Thermosetting Polymers. Issue 5 (18th February 2019) - Vassaux, Maxime; Sinclair, Robert C.; Richardson, Robin A.; Suter, James L.; Coveney, Peter V.
Abstract: Graphene continues to attract considerable attention from the materials science community through its potential for improving the mechanical properties of polymer thermosets, yet there remains considerable uncertainty over the underlying mechanisms. The effect of introducing graphene sheets to a typical thermosetting polymer network on mechanical behaviour is explored here through concurrently coupling molecular dynamics with a finite element solver. In this multiscale approach, Graphene is observed to act in two ways: as passive microscopic defects, dispersing crack propagation (high deformation); and as active geometric constraints, impeding polymer conformational changes (low deformation). By contrast, single‐scale atomistic simulations alone predict little measurable difference in the properties of the graphene‐enhanced epoxy resins as compared with the pure polymer case. The multiscale model predicts that epoxy resins reinforced with graphene nanoparticles exhibit enhanced overall elastoplastic properties, reducing strain energy dissipation by up to 70%. Importantly, this is only observed when taking into account the complex boundary conditions, mainly involving shear, arising from coupling physics on length scales separated by five orders of magnitude. The approach herein clearly highlights a novel role of graphene nanoparticles in actively constraining the surrounding polymer matrix, impeding local dissipative mechanisms, and resisting shear deformation. Abstract : A concurrent multiscale modeling approach is used to simulate the material properties of macroscopic graphene–epoxy nanocomposites with chemical specificity. Here, graphene acts in two ways: as passive microscopic defects, dispersing crack propagation; and as active geometric constraints, impeding polymer conformational changes. At the continuum level represented by finite elements, graphene is found to enhance the elastoplastic properties of epoxy nanocomposites.